Alteraciones de la materia orgánica y la repelencia del suelo al agua en una zona afectada por incendios forestales en parte de la microcuenca del Saloya. - Rivera Gárate, Carmen Amanda (2015)
The study shows the soil changes as a result of forest fires and the prescription in two areas that are part of Saloya River at south west of Quito; the study has a base in analysis of several publications by scientists who have developed this subject under some techniques using field and laboratory for several years. The soil is a complex system, for that reason is not feasible to standardize the effects of forest fires, several authors agree that depends on the intensity - severity of the fire, thus it is important to evaluate changes in the physical chemical properties of the soil; therefore the behavior of the variables such as pH, electrical conductivity, texture, carbon, nitrogen and water repellency is analyzed. These parameters are important since pH affects microbial activity; the texture in the water retention capacity; the organic matter affects control soil loss, the repellency can cause changes hydrological and geomorphological lead in the soil, and the interrelationships of these factors allow assessing the quality of these soils. The results of this study show that in zone 1, the pH, organic matter and repellency increased, while in zone 2 the pH and organic matter decreased, and the repellency changed due to the intensity and severity of fire in each zones.